Novel oxidative stress- and ferroptosis-related gene prognostic signature for erectile dysfunction - Meijun Liu; Maobin Yu; ZiYang Ma; Zilong Xu; Tao Zhang; Hongsen Zeng; Ze Li; XiYu Dang; Peihai Zhang (Egyptian Journal of Medical Human Genetics)
Abstract Background Studies have suggested that Guizhi Jia Longgu Muli decoction (GuiZhiJiaLongGuMuLiTang) has a therapeutic effect on erectile dysfunction (ED), even though how it works is still not fully understood. Methods In this research, transcriptome data related to ED were extracted from the GEO database. The candidate target genes were obtained by intersecting the differentially expressed genes (DEGs) screened using the software package limma, oxidative stress-related genes (OSRGs), ferroptosis-related genes (FRGs), and the target genes of the chemically active ingredients of GuiZhiJiaLongGuMuLiTang. Enrichment analyses of these candidate target genes were conducted using ClusterProfiler, and the key chemically active ingredient-candidate target gene-KEGG pathway network was constructed using Cytoscape. Then, the key target genes of ED were identified through an analysis of protein–protein interactions (PPIs). Additionally, a gene set enrichment analysis (GSEA) was performed to investigate the functions of the key target genes, and the mRNA-miRNA and TF-mRNA regulatory networks were developed to explore the potential regulation of these key genes. Furthermore, the intermolecular interactions between key target genes and key chemically active ingredients of GuiZhiJiaLongGuMuLiTang were studied using molecular docking analysis. Results Fifteen candidate target genes were associated with the HIF-1 signaling pathway, of which EGFR, PPARG, SLC2A1, and SRC were screened as the key target genes for ED. Notably, these key target genes were associated with oxidative phosphorylation, focal adhesion, and ECM–receptor interaction. The miRNA-mRNA and TF-mRNA regulatory networks were constructed, and it was observed that EGR1 could regulate EGFR and PPARG, TP53 could regulate EGFR and SLC2A1, and SP1 could regulate EGFR and SRC simultaneously. The miRNAs hsa-miR-1-3p, hsa-miR-218-5p, hsa-miR-138-5p, and hsa-miR-27a-3p were the common miRNAs of EGFR and PPARG. Furthermore, quercetin was the key chemically active ingredient of GuiZhiJiaLongGuMuLiTang, with the docking affinity between SLC2A1 and quercetin being the highest. Conclusion This study identified four key target genes related to oxidative stress and ferroptosis in ED: EGFR, PPARG, SLC2A1, and SRC, along with quercetin, an active compound in GuiZhiJiaLongGuMuLiTang. These results enrich the research on the mechanism of Guizhi Jia Longgu Muli decoction in treating erectile dysfunction.